1999
DOI: 10.1097/00004479-199910000-00004
|View full text |Cite
|
Sign up to set email alerts
|

An Overview: Health Centers at the Crossroads

Abstract: Health centers' flexibility in meeting changing political and economic demands throughout their history has allowed them to evolve and expand. In 1997, they served 8.3 million patients--40% uninsured and 35% Medicaid recipients. Thus far, most centers have been able to balance their mission of serving the underserved with economic survival. However, their future viability is threatened, by downward pressure on revenues, coinciding more frequently with growing numbers of uninsured patients. The centers' value a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…In addition to blacks, this study found decreases in LBW for Hispanics (5.6% vs. 6.5%) and Asians (6.6% vs. 7.5%) in CHCs compared to the general U.S. population. These decreases were all the more impressive due to the overall higher risk profiles of those attending CHCs (Forrest and Whelan 2000;Freeman, Kiecolt, and Allen 1982;Gardner 1993;Lefkowitz and Todd 1999;Regan et al 2003), and were still lower than the white LBW rate in both CHCs (8.2%) and in the national low-SES population (9.1%). These better overall birth outcomes for Hispanics versus whites, even among vulnerable groups in CHCs, have been previously attributed to acculturation factors (Callister and Birkhead 2002).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition to blacks, this study found decreases in LBW for Hispanics (5.6% vs. 6.5%) and Asians (6.6% vs. 7.5%) in CHCs compared to the general U.S. population. These decreases were all the more impressive due to the overall higher risk profiles of those attending CHCs (Forrest and Whelan 2000;Freeman, Kiecolt, and Allen 1982;Gardner 1993;Lefkowitz and Todd 1999;Regan et al 2003), and were still lower than the white LBW rate in both CHCs (8.2%) and in the national low-SES population (9.1%). These better overall birth outcomes for Hispanics versus whites, even among vulnerable groups in CHCs, have been previously attributed to acculturation factors (Callister and Birkhead 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Overall, CHCs had LBW rates that were similar to the total U.S. population (7.5% vs. 7.7%) and lower than the national low-SES population rate of 8.2% in 2001. This is impressive given that CHCs largely serve uninsured and low-SES populations who are at greater risk of poor outcomes (Forrest and Whelan 2000;Freeman, Kiecolt, and Allen 1982;Gardner 1993;Lefkowitz and Todd 1999;Regan et al 2003). This study further found that black-white disparity in LBW rates (inclusive of VLBW) was 3.3 percentage points in CHCs compared to 5.8 percentage points among low-SES mothers nationally and 6.2 percentage points for the total U.S. population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much morbidity could be prevented, however, if an efficient system of primary care existed for patients in medically underserved areas (1). To this end, in 1965, the federal government funded neighborhood health centers that were later codified as community, migrant, and homeless health centers through section 330 of the Public Health Service Act (2). The ϳ1,000 current federally supported health centers are an important source of primary care for 11 million medically underserved Americans (3).…”
mentioning
confidence: 99%
“…Research conducted on community health centres as a type of health service delivery organisation has indeed shown that their preventive and health promotion services can be vulnerable in a context of budgetary cutbacks. In the USA, for example, reductions in funding for many community health centres in the early 1970s had a negative impact on PHP services; sectors such as environmental health services, nutrition and health education were reduced or eliminated (Patton 1990, Lefkowitz & Todd 1999). A recent analysis of the situation in another Canadian province (Ontario) expressed concerns about the impact that upcoming reforms might have on the capacity of community health centres to influence health determinants (Suschnigg 2001).…”
Section: Introductionmentioning
confidence: 99%